Gender, technology and innovation: the role of women in Indian micro, small and medium enterprises. (26th April 2022) - Singh, Anurag; Das, Ujjwal; Kumar, Sharad
Innovation is the buzzword for all-round socio-economic development of nations, globally. It is considered as a method to increase productivity, processes new products, or services, playing a major role in socioeconomic change. Innovation becomes a tool for solving societal problems and economic development. It has also been seen as a process of qualitative change taking place in historical times. However, in innovation literature, the role of women in innovation received not much attention as it's deserved to be credited in academic and practice research. Innovation-based research and practices have not focused on gender differences. The role of women in innovation activities cannot be ignored. In this article, we present the role of women in selected Indian innovative Micro Small and Medium Enterprises (MSMEs) and the barriers they are facing. Based on our findings and literature, we also put forth several policy recommendations, to promote and encourage women entrepreneurship in India, viz. government support towards access to finance, training, and encouragement for innovation at educational and organisational levels.